Pendampingan Digital UMKM Saung Bambu Cisalak melalui Implementasi Aplikasi Griyo POS dalam Penguatan Ekonomi Kreatif Desa Cireundeu - Susilowati Susilowati; Ida Maelani; Dwi Nova Holisiah; Jesika Mardiana (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting rural economic growth. However, many MSMEs still face challenges in financial administration due to the use of poorly organized manual bookkeeping systems. This study aims to describe the digital mentoring process for the Saung Bambu Cisalak MSME in Cireundeu Village through the implementation of the Griyo POS application and to analyze its impact on strengthening the village’s creative economy. This research employs a qualitative approach using the Participatory Action Research (PAR) model, which actively involves MSME actors in all stages of the activity. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of the Griyo POS application improves the accuracy of transaction recording, enhances inventory management efficiency, and increases MSME actors’ understanding of the importance of financial data for business decision-making. This mentoring program contributes to improving the professionalism of MSME management and has the potential to strengthen the creative economy ecosystem in Cireundeu Village.